Affecting brand loyalty intention: The effects of UGC and shopping searches via Facebook. Issue 3 (3rd July 2018) - Mazzucchelli, Alice; Chierici, Roberto; Ceruti, Francesca; Chiacchierini, Claudio; Godey, Bruno; Pederzoli, Daniele
ABSTRACT: Despite the fact that social networking sites (SNSs) provide new opportunities for firms and brands, there is still a little understanding of how user-generated contents (UGC) and shopping-related research via Facebook (FB) affects brand loyalty intention in the luxury fashion context. The present work develops a conceptual model to empirically analyze how brand loyalty intention is affected by customers' trust in a brand's FB page, by their willingness to utilize brand's FB page for shopping-related searches, and by three different types of UGC: peer recommendations, informational support and emotional support. In order to fulfill this aim, the study examines 277 Millennials and the Victoria's Secret FB page. Structural equation model results reveal that online shopping-related searches, peer recommendations and social support have significant positive effects on customers' trust. Moreover, the research points out a significant positive effect between customers' trust and their brand loyalty intention, supporting marketers to better understand the role played by trusted UGC. The research provides interesting insights, for both academic and practitioners, because it contributes to the existing body of knowledge in the field of brand and social media marketing. Moreover, UGC, especially informational support, could enable firms to influence consumers' behavior positively and to transform their brands' FB pages into trusted ones.